1985
DOI: 10.1007/bf01806010
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated antigen TAG-72: Correlation of expression in primary and metastatic breast carcinoma lesions

Abstract: Variability of tumor-associated antigens among and within human tumor cell groups presents a potential problem in the development and optimization of immunodiagnostic and therapeutic procedures for cancer. We determined the degree of expression of a tumor-associated antigen in the primary and metastatic lesions of 23 patients with infiltrating ductal carcinoma; this was accomplished using monoclonal antibody B72.3, an IgG1 generated against membrane-enriched fractions of human metastatic breast carcinomas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…This delay did not seem of consequence, since other authors have demonstrated the antigenic content seems to remain similar in breast cancer metastatic tissue when compared to the original primary tumor [16]. A similar case can be made for NPGP detected by Mc5.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…This delay did not seem of consequence, since other authors have demonstrated the antigenic content seems to remain similar in breast cancer metastatic tissue when compared to the original primary tumor [16]. A similar case can be made for NPGP detected by Mc5.…”
Section: Resultssupporting
confidence: 53%
“…A similar case can be made for NPGP detected by Mc5. This antigen is the same antigen bound by DF3 in previous studies [16]. When binding of Mc5 to 9 primary breast tumors was compared to the binding of Mc5 to their metastases, the scoring indexes were not different statistically from each other as tested by t-test, U-test, and ANOVA (unpublished results).…”
Section: Resultsmentioning
confidence: 98%
“…The numbers on the top of the bars indicate the number of samples used for each study. References are indicated at the base of each bar, including [56,57,58,59,60,61,62] that are not quoted elsewhere in the text. SCC: Squamous cell carcinoma, AC: adenocarcinoma.…”
Section: Stn Immunodetection In Tissues and Tumorsmentioning
confidence: 99%
“…Early studies identified the sTn as a marker for diagnosis and prognosis in cancer, and later work focused on using sTn as a potential therapeutic target. sTn neo- or over-expression has been described in many types of epithelial cancer including: gastric [ 5 ], colon [ 6 ], breast [ 7 , 8 ], lung [ 9 ], oesophageal [ 10 ], pancreatic [ 11 ], prostate [ 12 , 13 ], bladder [ 14 ], and endometrial cancer [ 15 ]. Studies suggest that sTn expression has primarily been detected at the apical or luminal surface of tissue and tends to occur in early carcinogenesis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%